ФАРҒОНА-ТОШКЕНТ МАҚОМ ЙЎНАЛИШИНИНГ ФАЛСАФИЙ МАСАЛАСИГА ДОИР (Scientific journal of the Fergana State University, 2023)
The article analyzes the views on the formation of the statysa of Macоm Fergana-Tаshkent's direction, as well as the brochures of thinkers of Central Asia on Macom and the history of the development of the role of music culture.